(* Title: HOL/Computational_Algebra/Polynomial_FPS.thy
Author: Manuel Eberl, TU München
*)
section \Converting polynomials to formal power series\
theory Polynomial_FPS
imports Polynomial Formal_Power_Series
begin
context
includes fps_notation
begin
definition fps_of_poly where
"fps_of_poly p = Abs_fps (coeff p)"
lemma fps_of_poly_eq_iff: "fps_of_poly p = fps_of_poly q \ p = q"
by (simp add: fps_of_poly_def poly_eq_iff fps_eq_iff)
lemma fps_of_poly_nth [simp]: "fps_of_poly p $ n = coeff p n"
by (simp add: fps_of_poly_def)
lemma fps_of_poly_const: "fps_of_poly [:c:] = fps_const c"
proof (subst fps_eq_iff, clarify)
fix n :: nat show "fps_of_poly [:c:] $ n = fps_const c $ n"
by (cases n) (auto simp: fps_of_poly_def)
qed
lemma fps_of_poly_0 [simp]: "fps_of_poly 0 = 0"
by (subst fps_const_0_eq_0 [symmetric], subst fps_of_poly_const [symmetric]) simp
lemma fps_of_poly_1 [simp]: "fps_of_poly 1 = 1"
by (simp add: fps_eq_iff)
lemma fps_of_poly_1' [simp]: "fps_of_poly [:1:] = 1"
by (subst fps_const_1_eq_1 [symmetric], subst fps_of_poly_const [symmetric])
(simp add: one_poly_def)
lemma fps_of_poly_numeral [simp]: "fps_of_poly (numeral n) = numeral n"
by (simp add: numeral_fps_const fps_of_poly_const [symmetric] numeral_poly)
lemma fps_of_poly_numeral' [simp]: "fps_of_poly [:numeral n:] = numeral n"
by (simp add: numeral_fps_const fps_of_poly_const [symmetric] numeral_poly)
lemma fps_of_poly_fps_X [simp]: "fps_of_poly [:0, 1:] = fps_X"
by (auto simp add: fps_of_poly_def fps_eq_iff coeff_pCons split: nat.split)
lemma fps_of_poly_add: "fps_of_poly (p + q) = fps_of_poly p + fps_of_poly q"
by (simp add: fps_of_poly_def plus_poly.rep_eq fps_plus_def)
lemma fps_of_poly_diff: "fps_of_poly (p - q) = fps_of_poly p - fps_of_poly q"
by (simp add: fps_of_poly_def minus_poly.rep_eq fps_minus_def)
lemma fps_of_poly_uminus: "fps_of_poly (-p) = -fps_of_poly p"
by (simp add: fps_of_poly_def uminus_poly.rep_eq fps_uminus_def)
lemma fps_of_poly_mult: "fps_of_poly (p * q) = fps_of_poly p * fps_of_poly q"
by (simp add: fps_of_poly_def fps_times_def fps_eq_iff coeff_mult atLeast0AtMost)
lemma fps_of_poly_smult:
"fps_of_poly (smult c p) = fps_const c * fps_of_poly p"
using fps_of_poly_mult[of "[:c:]" p] by (simp add: fps_of_poly_mult fps_of_poly_const)
lemma fps_of_poly_sum: "fps_of_poly (sum f A) = sum (\x. fps_of_poly (f x)) A"
by (cases "finite A", induction rule: finite_induct) (simp_all add: fps_of_poly_add)
lemma fps_of_poly_sum_list: "fps_of_poly (sum_list xs) = sum_list (map fps_of_poly xs)"
by (induction xs) (simp_all add: fps_of_poly_add)
lemma fps_of_poly_prod: "fps_of_poly (prod f A) = prod (\x. fps_of_poly (f x)) A"
by (cases "finite A", induction rule: finite_induct) (simp_all add: fps_of_poly_mult)
lemma fps_of_poly_prod_list: "fps_of_poly (prod_list xs) = prod_list (map fps_of_poly xs)"
by (induction xs) (simp_all add: fps_of_poly_mult)
lemma fps_of_poly_pCons:
"fps_of_poly (pCons (c :: 'a :: semiring_1) p) = fps_const c + fps_of_poly p * fps_X"
by (subst fps_mult_fps_X_commute [symmetric], intro fps_ext)
(auto simp: fps_of_poly_def coeff_pCons split: nat.split)
lemma fps_of_poly_pderiv: "fps_of_poly (pderiv p) = fps_deriv (fps_of_poly p)"
by (intro fps_ext) (simp add: fps_of_poly_nth coeff_pderiv)
lemma fps_of_poly_power: "fps_of_poly (p ^ n) = fps_of_poly p ^ n"
by (induction n) (simp_all add: fps_of_poly_mult)
lemma fps_of_poly_monom: "fps_of_poly (monom (c :: 'a :: comm_ring_1) n) = fps_const c * fps_X ^ n"
by (intro fps_ext) simp_all
lemma fps_of_poly_monom': "fps_of_poly (monom (1 :: 'a :: comm_ring_1) n) = fps_X ^ n"
by (simp add: fps_of_poly_monom)
lemma fps_of_poly_div:
assumes "(q :: 'a :: field poly) dvd p"
shows "fps_of_poly (p div q) = fps_of_poly p / fps_of_poly q"
proof (cases "q = 0")
case False
from False fps_of_poly_eq_iff[of q 0] have nz: "fps_of_poly q \ 0" by simp
from assms have "p = (p div q) * q" by simp
also have "fps_of_poly \ = fps_of_poly (p div q) * fps_of_poly q"
by (simp add: fps_of_poly_mult)
also from nz have "\ / fps_of_poly q = fps_of_poly (p div q)"
by (intro nonzero_mult_div_cancel_right) (auto simp: fps_of_poly_0)
finally show ?thesis ..
qed simp
lemma fps_of_poly_divide_numeral:
"fps_of_poly (smult (inverse (numeral c :: 'a :: field)) p) = fps_of_poly p / numeral c"
proof -
have "smult (inverse (numeral c)) p = [:inverse (numeral c):] * p" by simp
also have "fps_of_poly \ = fps_of_poly p / numeral c"
by (subst fps_of_poly_mult) (simp add: numeral_fps_const fps_of_poly_pCons)
finally show ?thesis by simp
qed
lemma subdegree_fps_of_poly:
assumes "p \ 0"
defines "n \ Polynomial.order 0 p"
shows "subdegree (fps_of_poly p) = n"
proof (rule subdegreeI)
from assms have "monom 1 n dvd p" by (simp add: monom_1_dvd_iff)
thus zero: "fps_of_poly p $ i = 0" if "i < n" for i
using that by (simp add: monom_1_dvd_iff')
from assms have "\monom 1 (Suc n) dvd p"
by (auto simp: monom_1_dvd_iff simp del: power_Suc)
then obtain k where k: "k \ n" "fps_of_poly p $ k \ 0"
by (auto simp: monom_1_dvd_iff' less_Suc_eq_le)
with zero[of k] have "k = n" by linarith
with k show "fps_of_poly p $ n \ 0" by simp
qed
lemma fps_of_poly_dvd:
assumes "p dvd q"
shows "fps_of_poly (p :: 'a :: field poly) dvd fps_of_poly q"
proof (cases "p = 0 \ q = 0")
case False
with assms fps_of_poly_eq_iff[of p 0] fps_of_poly_eq_iff[of q 0] show ?thesis
by (auto simp: fps_dvd_iff subdegree_fps_of_poly dvd_imp_order_le)
qed (insert assms, auto)
lemmas fps_of_poly_simps =
fps_of_poly_0 fps_of_poly_1 fps_of_poly_numeral fps_of_poly_const fps_of_poly_fps_X
fps_of_poly_add fps_of_poly_diff fps_of_poly_uminus fps_of_poly_mult fps_of_poly_smult
fps_of_poly_sum fps_of_poly_sum_list fps_of_poly_prod fps_of_poly_prod_list
fps_of_poly_pCons fps_of_poly_pderiv fps_of_poly_power fps_of_poly_monom
fps_of_poly_divide_numeral
lemma fps_of_poly_pcompose:
assumes "coeff q 0 = (0 :: 'a :: idom)"
shows "fps_of_poly (pcompose p q) = fps_compose (fps_of_poly p) (fps_of_poly q)"
using assms by (induction p rule: pCons_induct)
(auto simp: pcompose_pCons fps_of_poly_simps fps_of_poly_pCons
fps_compose_add_distrib fps_compose_mult_distrib)
lemmas reify_fps_atom =
fps_of_poly_0 fps_of_poly_1' fps_of_poly_numeral' fps_of_poly_const fps_of_poly_fps_X
text \
The following simproc can reduce the equality of two polynomial FPSs two equality of the
respective polynomials. A polynomial FPS is one that only has finitely many non-zero
coefficients and can therefore be written as @{term "fps_of_poly p"} for some
polynomial \p\.
This may sound trivial, but it covers a number of annoying side conditions like
@{term "1 + fps_X \ 0"} that would otherwise not be solved automatically.
\
ML \
(* TODO: Support for division *)
signature POLY_FPS = sig
val reify_conv : conv
val eq_conv : conv
val eq_simproc : cterm -> thm option
end
structure Poly_Fps = struct
fun const_binop_conv s conv ct =
case Thm.term_of ct of
(Const (s', _) $ _ $ _) =>
if s = s' then
Conv.binop_conv conv ct
else
raise CTERM ("const_binop_conv", [ct])
| _ => raise CTERM ("const_binop_conv", [ct])
fun reify_conv ct =
let
val rewr = Conv.rewrs_conv o map (fn thm => thm RS @{thm eq_reflection})
val un = Conv.arg_conv reify_conv
val bin = Conv.binop_conv reify_conv
in
case Thm.term_of ct of
(Const (@{const_name "fps_of_poly"}, _) $ _) => ct |> Conv.all_conv
| (Const (@{const_name "Groups.plus"}, _) $ _ $ _) => ct |> (
bin then_conv rewr @{thms fps_of_poly_add [symmetric]})
| (Const (@{const_name "Groups.uminus"}, _) $ _) => ct |> (
un then_conv rewr @{thms fps_of_poly_uminus [symmetric]})
| (Const (@{const_name "Groups.minus"}, _) $ _ $ _) => ct |> (
bin then_conv rewr @{thms fps_of_poly_diff [symmetric]})
| (Const (@{const_name "Groups.times"}, _) $ _ $ _) => ct |> (
bin then_conv rewr @{thms fps_of_poly_mult [symmetric]})
| (Const (@{const_name "Rings.divide"}, _) $ _ $ (Const (@{const_name "Num.numeral"}, _) $ _))
=> ct |> (Conv.fun_conv (Conv.arg_conv reify_conv)
then_conv rewr @{thms fps_of_poly_divide_numeral [symmetric]})
| (Const (@{const_name "Power.power"}, _) $ Const (@{const_name "fps_X"},_) $ _) => ct |> (
rewr @{thms fps_of_poly_monom' [symmetric]})
| (Const (@{const_name "Power.power"}, _) $ _ $ _) => ct |> (
Conv.fun_conv (Conv.arg_conv reify_conv)
then_conv rewr @{thms fps_of_poly_power [symmetric]})
| _ => ct |> (
rewr @{thms reify_fps_atom [symmetric]})
end
fun eq_conv ct =
case Thm.term_of ct of
(Const (@{const_name "HOL.eq"}, _) $ _ $ _) => ct |> (
Conv.binop_conv reify_conv
then_conv Conv.rewr_conv @{thm fps_of_poly_eq_iff[THEN eq_reflection]})
| _ => raise CTERM ("poly_fps_eq_conv", [ct])
val eq_simproc = try eq_conv
end
\
simproc_setup poly_fps_eq ("(f :: 'a fps) = g") = \K (K Poly_Fps.eq_simproc)\
lemma fps_of_poly_linear: "fps_of_poly [:a,1 :: 'a :: field:] = fps_X + fps_const a"
by simp
lemma fps_of_poly_linear': "fps_of_poly [:1,a :: 'a :: field:] = 1 + fps_const a * fps_X"
by simp
lemma fps_of_poly_cutoff [simp]:
"fps_of_poly (poly_cutoff n p) = fps_cutoff n (fps_of_poly p)"
by (simp add: fps_eq_iff coeff_poly_cutoff)
lemma fps_of_poly_shift [simp]: "fps_of_poly (poly_shift n p) = fps_shift n (fps_of_poly p)"
by (simp add: fps_eq_iff coeff_poly_shift)
definition poly_subdegree :: "'a::zero poly \ nat" where
"poly_subdegree p = subdegree (fps_of_poly p)"
lemma coeff_less_poly_subdegree:
"k < poly_subdegree p \ coeff p k = 0"
unfolding poly_subdegree_def using nth_less_subdegree_zero[of k "fps_of_poly p"] by simp
(* TODO: Move ? *)
definition prefix_length :: "('a \ bool) \ 'a list \ nat" where
"prefix_length P xs = length (takeWhile P xs)"
primrec prefix_length_aux :: "('a \ bool) \ nat \ 'a list \ nat" where
"prefix_length_aux P acc [] = acc"
| "prefix_length_aux P acc (x#xs) = (if P x then prefix_length_aux P (Suc acc) xs else acc)"
lemma prefix_length_aux_correct: "prefix_length_aux P acc xs = prefix_length P xs + acc"
by (induction xs arbitrary: acc) (simp_all add: prefix_length_def)
lemma prefix_length_code [code]: "prefix_length P xs = prefix_length_aux P 0 xs"
by (simp add: prefix_length_aux_correct)
lemma prefix_length_le_length: "prefix_length P xs \ length xs"
by (induction xs) (simp_all add: prefix_length_def)
lemma prefix_length_less_length: "(\x\set xs. \P x) \ prefix_length P xs < length xs"
by (induction xs) (simp_all add: prefix_length_def)
lemma nth_prefix_length:
"(\x\set xs. \P x) \ \P (xs ! prefix_length P xs)"
by (induction xs) (simp_all add: prefix_length_def)
lemma nth_less_prefix_length:
"n < prefix_length P xs \ P (xs ! n)"
by (induction xs arbitrary: n)
(auto simp: prefix_length_def nth_Cons split: if_splits nat.splits)
(* END TODO *)
lemma poly_subdegree_code [code]: "poly_subdegree p = prefix_length (op = 0) (coeffs p)"
proof (cases "p = 0")
case False
note [simp] = this
define n where "n = prefix_length (op = 0) (coeffs p)"
from False have "\k. coeff p k \ 0" by (auto simp: poly_eq_iff)
hence ex: "\x\set (coeffs p). x \ 0" by (auto simp: coeffs_def)
hence n_less: "n < length (coeffs p)" and nonzero: "coeffs p ! n \ 0"
unfolding n_def by (auto intro!: prefix_length_less_length nth_prefix_length)
show ?thesis unfolding poly_subdegree_def
proof (intro subdegreeI)
from n_less have "fps_of_poly p $ n = coeffs p ! n"
by (subst coeffs_nth) (simp_all add: degree_eq_length_coeffs)
with nonzero show "fps_of_poly p $ prefix_length (op = 0) (coeffs p) \ 0"
unfolding n_def by simp
next
fix k assume A: "k < prefix_length (op = 0) (coeffs p)"
also have "\ \ length (coeffs p)" by (rule prefix_length_le_length)
finally show "fps_of_poly p $ k = 0"
using nth_less_prefix_length[OF A]
by (simp add: coeffs_nth degree_eq_length_coeffs)
qed
qed (simp_all add: poly_subdegree_def prefix_length_def)
end
end